Impact of in-hospital oral beta-blockers initiation on long-term outcomes in ST-elevation myocardial infarction patients with cardiogenic shock - Gao, Xiaojin; Liu, Mengyuan; Xu, Jing; Li, Ling; Chen, Min; Lang, Xinyue; Jia, Shaobin; Ning, Bin; Xu, Haiyan; Song, Lei; Wu, Yuan; Zhang, Jun; et al. (Frontiers in Medicine, 2025)
BackgroundEarly revascularization enables ST-elevation myocardial infarction (STEMI) patients with cardiogenic shock (CS) to initiate oral beta-blockers once hemodynamic stability is achieved, but the impact of such initiation on prognosis remains unknown. We aimed to describe the clinical use of oral beta-blockers and assess its impact on long-term outcomes in STEMI patients with CS in a real-world setting.Materials and methodsThe China Acute Myocardial Infarction registry (CAMI) is a prospective observational study that enrolls patients with acute myocardial infarction from three-level hospitals across 31 administrative regions in mainland China. Among 19,112 STEMI patients in the CAMI registry, a total of 744 STEMI patients who presented with CS at admission were analyzed. Multivariate regression models were used to evaluate the impact of in-hospital oral beta-blockers on 2-year outcomes. Inverse probability treatment weighting (IPTW) score was further used to address biases between the groups with and without oral beta-blockers. The primary endpoint was all-cause death.Results42.7% (n = 318) of the patients initiated in-hospital oral beta-blockers; these patients were in better states and more likely to receive primary percutaneous coronary intervention and secondary prevention at discharge. The crude 2-year all-cause mortality was 41.7%, with a lower rate in patients who received oral beta-blockers (24.2% vs. 54.8%, P < 0.001). However, after multivariate adjustment, patients who received oral beta-blockers showed a non-significant increase in 2-year mortality compared with non-users (HR = 1.29, 95% CI: 0.95–1.75, P = 0.099), and this increase became statistically significant in the subgroup of county-level hospitals (HR = 1.79, 95% CI: 1.03–3.09, P = 0.038, P-interaction = 0.010). Furthermore, after balancing the baseline covariates using IPTW and further adjusting for discharge medications, initiation of oral beta-blockers during hospitalization increased the risk of 2-year all-cause mortality (HR = 1.59, 95% CI: 1.18–2.13, P = 0.002).ConclusionNo benefit of in-hospital oral beta-blockers initiation on long-term all-cause mortality was found in Chinese STEMI patients with CS, and a trend toward increased mortality existed, especially in small-scale hospitals with insufficient experience in CS treatment.